A longitudinal perspective on car ownership and use in relation with income inequalities in the Paris metropolitan area. Issue 2 (4th March 2017) - Cornut, Benoît; Madre, Jean-Loup
ABSTRACT: The objective is to analyse the evolution of car ownership and use in the Paris region according to the standard of living of households and the place of residence (Paris, inner suburbs and outer suburbs). Based on annual panel surveys from 1974 to 2013, we show that a maximum of car use has been reached in the 1990s in the Paris region but the date of appearance of car ownership and use saturation differs according to the zone of residence (earlier in the City of Paris). The Gini index and the Q4/Q1 ratio are also computed to describe the evolution of inequalities in the population. In the Paris region, car ownership and use inequalities have strongly reduced since the 1970s. However, the levels of inequalities are higher in dense areas than in the outer suburbs where the necessity to own a car tends to homogenise travel behaviour. Last, if the Gini index is low because global inequalities are weak, inequalities remain important for low-income groups, especially in the outer suburbs where the indicators have to be interpreted as indicators of inequity.